Effect of buprofezin on the growth, development and morphometric parameters of Spodoptera litura (Fabricius) (Order: Lepidoptera, Family: Noctuidae) adult: Effect of Buprofezin against Spodoptera litura (Fabricius) adult (Journal of the Bangladesh Agricultural University, 2019)
The experiments were conducted to know the efficacy of Buprofezin (Award 40 SC), an insect growth regulator against 2nd instar larvae of Spodoptera litura (Fabricius) under laboratory conditions (insect rearing was done at room temperature and relative humidity that is 260C-300C and 65-80% relative humidity) at three different concentrations viz. 200, 400, and 600 ppm through three different application methods like direct or topical, indirect or leaf-dip and combined. The experiment was laid out in complete randomized design (CRD) with three replications and ten 2nd instar larvae of Spodoptera litura were used for each replication. Results revealed that this growth regulator strongly arrested the growth and development of S. litura (Fabricius) from larval stage to adult. The treated data were recorded after adult emergence and compared with untreated control adult. The results clearly showed that Buprofezin had significant effect on the inhibition of adult weight; wing length and width compared to control and consequence were clearly dose, time and method dependent. As well as we are hopeful because we found some abnormal adult from the treated larvae that may increase the potentiality of Buprofezin as an excellent tool of IPM. The maximum, 54.53% adult weight reduction was recorded from 600 ppm of Buprofezin through combined application method which was followed by leaf-dip (46.41%) and topical application method (39.86%). Similarly, 23.13% wing length and 22.27% wing width were inhibited when larvae were treated with 600 ppm through combined application method compared to control. The 2nd best result was found from 400 ppm and leaf-dip application method. The dose, 200 ppm and topical application method was found to be less effective compared to the rest of the two doses or two application methods. So this is the demand of the current situation to evaluate this selective bio-rational molecules against S. litura as the alternatives of conventional insecticides to combat resistance development, effective larval control, inhibition of growth and development, to keep the  natural enemies safe and fit these molecules in IPM packages individually or combindly.J Bangladesh Agril Univ 17(4): 514–520, 2019